90 K superconductivity of clean Pb1212 epitaxial films. (16th June 2016) - Komori, S; Kondo, A; Kindo, K; Kakeya, I
Abstract: A single-phase Pb 1 − y Sr 2 Y 1 − x Ca x Cu 2 + y O 7 + δ (Pb1212) epitaxial film with T c, onset = 90 K has been grown using a two-step technique, which allows lattice relaxation near the film/substrate interface and reduction of Pb vacancies. Using the upper critical field measurement, the coherence lengths are derived to be 20 and 4.3 Å, along the ab -plane and c -axis, respectively. The value of the irreversibility field is found to be close to that of YBa2 Cu3 O7 . High magnetic field measurement has revealed normal state resistivity below T c and metallic behavior in the underdoped region.